2000
DOI: 10.1007/bf02796206
|View full text |Cite
|
Sign up to set email alerts
|

Urinary albumin excretion and transcapillary escape rate of albumin in malignancies

Abstract: Transcapillary escape rate of albumin was determined in 22 patients with different malignancies. In addition, urinary albumin excretion rate was measured in 24-h urine samples using a sensitive immunoassay. Increased urinary albumin excretion was defined as >/=20 microg/min according to conventional standards. Renal glomerular filtration and tubular function was estimated by 51Cr-EDTA plasma clearance and urinary beta 2-microglobulin, respectively. Median urinary albumin excretion rate was 15.0 microg/min (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…An elevated urinary albumin excretion in patients with malignancies has been reported previously. 19 Interestingly, although the precise underlying mechanism is unknown, it has been speculated that in this type of patient, the increased urinary albumin loss appears to be more of an isolated renal phenomenon than to be related to endothelial dysfunction, because a normal endothelial function was observed, as demonstrated by the transcapillary escape rate of albumin, which suggests an overall unaffected capillary permeability. The present study adds considerable data to the available information on urinary albumin excretion as a vascular risk factor because we have used the full range of UAC in studying the relationship with mortality and did not cluster UAC levels into several categories.…”
Section: Hillege Et Al Urinary Albumin Concentration and Mortalitymentioning
confidence: 81%
“…An elevated urinary albumin excretion in patients with malignancies has been reported previously. 19 Interestingly, although the precise underlying mechanism is unknown, it has been speculated that in this type of patient, the increased urinary albumin loss appears to be more of an isolated renal phenomenon than to be related to endothelial dysfunction, because a normal endothelial function was observed, as demonstrated by the transcapillary escape rate of albumin, which suggests an overall unaffected capillary permeability. The present study adds considerable data to the available information on urinary albumin excretion as a vascular risk factor because we have used the full range of UAC in studying the relationship with mortality and did not cluster UAC levels into several categories.…”
Section: Hillege Et Al Urinary Albumin Concentration and Mortalitymentioning
confidence: 81%
“…Some studies have indicated that the extent of albuminuria reflects disease severity, showing high levels in patients with metastatic disease and large tumor burden. Therefore, albuminuria has been suggested as a nonspecific malignancy marker, reflecting microvascular responses and altered glomerular permeability in response to malignant cell products such as cytokines 8,20. However, studies assessing the relationship between proteinuria and all-cause mortality in patients with colorectal cancer are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies observed that serum albumin is a prognostic factor of survival in various cancer entities, but also in sarcomas . Lower levels of serum albumin are believed to be indicative of an ongoing systemic response to tumor cell products and inflammatory cytokines …”
mentioning
confidence: 99%